Effects of hygroscopic and hydrophobic filters in the mucus clearance and bacterial barriers in patients with liver disease - Silva, Eliane Maria Carvalho; Isern, Maria Rita Montenegro; Massarollo, Paulo C. B.; Saldiva, Paulo Hilário Nascimento; Mies, Sérgio; Lorenzi- Filho, Geraldo (Brazilian Journal of Transplantation, 2005)
Objective: To compare the effects of the hydrophobic and hygroscopic filtering (HHF) in the physical properties and transportability of the mucus and lung infection rate. Material and Method: Thirty five patients included in this study where submitted to mechanical ventilation for more than 24 hours at the Liver Transplant’s Intensive Care Unit (ICU). Patients were randomized in two groups immediately after intubation. Group 1 (n= 19) used a BB100 hydrophobic filter, and Group 2 (n = 16) used a Humid-Vent Filter®. Light hygroscopic filter. The mean ages of the hydrophobic and hygroscopic groups were 52.4 + 13.0, and 45.5 + 16.4, respectively. Results: Patients had similar fraction of inspired volume of Oxygen, partial pressure of Oxygen / fraction of inspired Oxygen, minute/volume, to the hydric balance in the previous 24 hours, and to the sodium and bilirubin value. The mucus transportability was assessed through the ciliary transportation and cough. The adherence was measured by the contact angle. The filtering analysis as a bacterial barrier was assessed by the tracheal secretion culture. Conclusion: The physical properties of the mucus remained unchanged with the use of the HHF. Nevertheless, the transportation through cough was better in the hygroscopic group. Both HHF can be considered bacterial barriers, and they can reduce the occurrence of the ventilator-related pneumonia.